Electrically tunable window based on microwrinkled ZnO/Ag thin film - Shrestha, Milan (2019)
Micro-winkling can turn a transparent thin-film of zinc oxide (ZnO) to be ‘opaque’ that can be reversed by unfolding to restore back to the clear state. This principle was previously used to make a mechanically tunable window device. However, ZnO thin film cannot make a compliant electrode to enable electrical unfolding due to its insulator nature. This paper reports the use of multilayer thin films of 10nm silver (Ag) and 30nm thick ZnO to form a compliant electrode with electrically tunable transmittance. A dielectric elastomer actuator (DEA) with a pair of such compliant Ag/ZnO thin films on both sides of a polyacrylate elastomeric membrane (3M VHB 4910) makes an electrically tunable window device. The DEA without radial compression of the elastomer has wrinkle-free electrode. Hence, it is clear with a 47% in-line transmittance (for 550nm wavelength light). In the wrinkled form, under 10% radial compression, it becomes opaque (with less than 1% transmittance). A voltage induced areal expansion of 10% radial strain enables the electrical unfolding of the initial wrinkles. In addition, this device continues to work after 4000 cycles of unfolding and microwrinkling of Ag/ZnO. The performance of electrically tunable window device is comparable to the existing smart window technologies.